Maternal pre-existing diabetes and gestational diabetes and the prevalence of septal defects in the offspring. (3rd October 2022) - Hansson, M; Voegg, R O B; Blixenkrone-Moeller, E; Dannesbo, S; Dehn, A M; Phil, C; Sillesen, A S; Axelsson Raja, A; Damm, P; Reinhardt Mathiesen, E; Iversen, K; Bundgaard, H
Abstract: Background and introduction: Maternal pre-existing and gestational diabetes affect approximately 6% of all pregnancies in Denmark and are well known risk factors for congenital heart disease (CHD). Worldwide, CHD is the most common congenital defect and a leading cause of infant death. The association between maternal diabetes, and CHD in the offspring has previously been studied, however, these studies have been limited by small study cohorts and/or registry studies without systematic transthoracic echocardiography (TTE) of the children. Purpose: To assess the prevalence of atrial and ventricular septal defects (ASD and VSD) in children born to mothers with pre-existing or gestational diabetes by systematic TTE, in a large, population-based cohort of neonates. Method: Systematic, standardized TTE was performed in neonates included in a population-based cohort study between 2016 and 2018. For the present study, the prevalence of VSD in cases and controls was assessed in the entire cohort of neonates who underwent TTE within 30 days of birth, and in whom information regarding maternal diabetes was available (n=24, 921). The prevalence of ASD was assessed in a sub-cohort of neonates (n=12, 682) with the same inclusion criteria and in whom an interatrial communication had been classified as ASD or patent oval foramen according to a validated algorithm. ASD was defined as an interatrial communication with a defect size ≥4mm, a location in the inferior 1/3 of septum, or multiple communications. VSD was defined as flow across the interventricular septum in colour Doppler mode in one or more views. VSDs were classified as either muscular, perimembranous, or subarterial. Information about maternal pre-existing and gestational diabetes was collected from review of the mother's medical records and from an Obstetrical Database maintained by the participating hospitals. Cases were compared with controls, which here consists of the full cohort for VSD and sub-cohort for ASD, respectively, after excluding cases. Results: The median age at examination of the entire cohort was 11 days [interquartile range (IQR) 7; 14] and 48% were female. The prevalence of VSD in children with maternal diabetes was 3.1% compared with 3.3% among children of mothers without maternal diabetes, RR 1.00 (95% CI 0.99–1.01, p=0.771). There was no difference between cases and controls when comparing the prevalence of subtypes of VSD (table 1). In the sub-cohort of 12, 682 neonates assessed for ASD (median age at examination 12 days [IQR, 8; 15], 48% female), the presence of an ASD was found in 7.3% of cases compared to 5.9% among controls, RR 0.81 (95% CI 0.59–1.13, p=0.214). Conclusion: In a large population-based cohort of infants, we did not find an increased risk for ASD or VSD, nor any of the subtypes of VSD, among children born to mothers with pre-existing or gestational diabetes as compared to controls. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): The Capital Region of Denmarks Research Fund.The Research Council of Herlev and Gentofte Hospital.